Comparison of Induction at 40+10 Weeks with Induction at 40 weeks for Caesarean Section Rate and Perinatal Outcome in Postdate Pregnanciess - Yasmeen, Almas; Aslam, Rakhshanda; ., Fareeha; Malik, Laraib; Shafaqat, Hira; Tariq, Sana (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare caesarean section rate and perinatal outcome among women with postdate pregnancies having one previous scar induced at 40+10 weeks and 40 weeksStudy Design: Quasi-experimental study.Place and Duration of Study Obstetrics department, Pak Emirates Military Hospital Rawalpindi, Pakistan from Jan to Jun 2022Methodology:  The study was conducted on women with one previous scar who were booked cases in our department and did not have spontaneous vaginal delivery till 40 weeks of gestation. They were divided into two groups. One group had an induction of labor at 40 weeks, while the other had an induction at 40+10 weeks. Clinical parameters like rate of Caesarean section for delivery, meconium aspiration, hypoxic-ischemic encephalopathy, and meconium-stained liquor were compared in both groups.Results A total of 413 women with one previous scar and post-dated pregnancies were recruited for this study. Two groups were made for comparison. 182(44.1%) mothers had induction at 40 weeks, while 231(55.9%) had induction at 40+10 weeks. 208(50.3%) had a vaginal birth after the caesarean section, while 205(49.7%) underwent a Caesarean section. Statistical analysis revealed that more caesarean rate, meconium aspiration, hypoxic-ischemic encephalopathy, and meconium-stained liquor were found in the 40+10 weeks group (p-value